Understanding Thyroid Carcinoma: Clinical Manifestations, Diagnosis, and Management - Kusumadewi, Rima Cahyati; Rukmanggana Satya Pratiwi; Artiani Tresna Imut Exhasna; Gina Aulia Azizaturrahmah; Sastrawan, I Gede Pande Devin Agastya; Rosita Wenilia; Syihabul Muttaqin; Dita Supriantarini; M. Arya Rifqi Ilham; Walid Rivaldi Fatahillah; Eva Triani (Jurnal Biologi Tropis, 2024)
Thyroid carcinoma holds the 11th place in the incidence of new cancers, with a prevalence of 586,202 cases worldwide. The incidence of thyroid cancer in Indonesia reached 13,114 cases with 2,224 mortality in 2020. This literature review aims to provide information on thyroid cancer's clinical manifestations, diagnosis, and management. We conducted a literature searching from books, literature reviews, case studies, and guidelines from professional organizations such as the AJCC (American Joint Committee on Cancer) and European Society for Medical Oncology (ESMO) guideline. The initially noticed clinical manifestation of thyroid cancer is usually a painless lump or enlargement at the front-lower part of the neck. Diagnosis of thyroid cancer is done step-by-step from history taking, physical examination, laboratory testing of thyroid stimulating hormone and thyroglobulin, thyroid ultrasonography, and fine needle aspiration biopsy (FNAB). Management of thyroid cancer include pharmacological management, surgery, or/and radiotherapy according to the type and stage of the thyroid cancer. Early diagnosis and therapy of thyroid cancer are expected to improve the prognosis of thyroid cancer.